Overview of Coping Mechanism Mother of Children With Disabilities in SDLB Negeri Tompokersan Lumajang - Resita Ovina Intiyaskanti; Erti Ikhtiarini Dewi; Enggal Hadi Kurniyawan (Nursing and Health Sciences Journal (NHSJ), 2021)
Mothers who have children with disabilities have many problems and barriers. The research aims to describe mother’s coping mechanisms for children with disabilities in SDLB Negeri Tompokersan Lumajang. Respondents in this study were 54 mothers that were taken with purposive sampling technique with brief cope instrument. The result showed mother’s age have a median value of 39.50 years and the child's age have a median value of 11 years. Mothers who have children with disabilities have 1 child with disabilities in the family (96.3%) in order of disabled children in the main family of the first child (55.4%). The majority of mothers' last education is elementary school (35.2%) and The majority of the marital status is married (96.3%). Types of disabilities that are mostly experienced are intellectual disabilities (61.1%). The description of a mother’s coping mechanism in children with disabilities has a mean of 86.46. It is shown that the dominant indicators for respondents include religion (mothers believe there is wisdom in the problem), behavioral disengagement (mothers fulfill their education rights and provide therapy or medication), and substance use (mothers do not use drugs to protect themselves). Further researchers can identify mother’s motivation in caring for children with disabilities